A mango-shaped space : a novel - Mass, Wendy, 1967- (Little, Brown, 2005)
Afraid that she is crazy, thirteen-year-old Mia, who sees a special color with every letter, number, and sound, keeps this a secret until she becomes overwhelmed by school, changing relationships, and the death of her beloved cat, Mango.